(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The main objective of the study was to compare the level of postoperative pain among patients who have undergone abdominal surgery between before and after administration of foot and hand massage in experimental group and control group (routine therapy) as measured by numerical pain rating scale. The research design adopted was time series design. A total of fifty abdominal surgery patients who met inclusion criteria were selected by using purposive sampling technique. Foot and Hand massage was administered 3times a day for consecutive 3 days. In intervention group, 24 (96%) patients had severe pain during pre-test, and 25(100%) patients had moderate pain on the post-test day one. On day two, 19 (76%) patients had mild pain and on day three, 23(92%) had mild pain and 6(24%)had moderate pain. In comparison group 25(100%) patients had severe pain during pre-test, on the post-test’s day one, 25 (100%) patients had severe pain. On day two, 21 (84%) had severe pain and 4 (16%) had moderate pain. On day three, 7 (28%)patients had severe pain and 18 (72%) had moderate pain. None of them experienced no pain even at the third day in both the groups. The overall post-test mean and standard deviation of the intervention group is 3.2 ± 0.066. The calculated t value is 39.04 which is greater than the table value (3.53) at the level of p